2012
DOI: 10.1063/1.3688253
|View full text |Cite
|
Sign up to set email alerts
|

Roles of silica and lignin in horsetail (Equisetum hyemale), with special reference to mechanical properties

Abstract: This research deals with detailed analyses of silica and lignin distribution in horsetail with special reference to mechanical strength. Scanning electron images of a cross-section of an internode showed silica deposited densely only around the outer epidermis. Detailed histochemical analyses of lignin showed no lignin deposition in the silica-rich outer internodes of horsetail, while a characteristic lignin deposition was noticed in the vascular bundle in inner side of internodes. To analyze the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…These observations are in agreement with what was previously shown in the literature, i.e. that Si-deficient horsetail had fragile, weak stems which subsequently withered, while Si-supplemented Equisetum did not [12]. Within 2 weeks, the infected areas were completely necrotic.…”
Section: Si-deficient Horsetail Succumbed To Biotic Stressors After 1supporting
confidence: 93%
“…These observations are in agreement with what was previously shown in the literature, i.e. that Si-deficient horsetail had fragile, weak stems which subsequently withered, while Si-supplemented Equisetum did not [12]. Within 2 weeks, the infected areas were completely necrotic.…”
Section: Si-deficient Horsetail Succumbed To Biotic Stressors After 1supporting
confidence: 93%
“…There are structures which appear more heavily silicified than others and their propensities for silicification are probably determined by the respective densities of the molecular structures acting as templates of the precipitation process. We have identified the hemicellulose callose as one such molecular template for biological silicification ( Law and Exley, 2011 ) and others will probably include precursors to and components of plant cell walls ( Fleck et al, 2011 ; Fernández Honaine and Osterrieth, 2012 ; Yamanaka et al, 2012 ; Fernández Honaine et al, 2013 ; Leroux et al, 2013 ; Zhang et al, 2013 ).…”
Section: Templating Silicificationmentioning
confidence: 99%
“…1,2 Popularly, the stems of the plant are used for the production of an infusion that acts as a diuretic, digestive, anti-anemic, anti-inflammatory, and antimicrobial, and is also employed to treat gonorrhea, diarrhea, kidney infections, and bladder and eye diseases. 3,4 Although there are few reports of the antimicrobial activity of E. hyemale in the literature, a study carried out by our research group demonstrated the antimicrobial activity of crude extract and fractions, as well as the ability of these extracts to inhibit the formation of biofilm formed by P. aeruginosa (01). These results were justified by the presence of high levels of phenyl compounds in the plant structure.…”
Section: Introductionmentioning
confidence: 99%